Argentine Curriculum in Covid-19 Pandemic - Ferry Ferdianto; Iwan Junaedi; Mulyono Mulyono (AlphaMath : Journal of Mathematics Education, 2021)
Corona virus disease 2019 (Covid-19) began to spread in Argentina in March 2020, based on data until August 25, 2020, in Argentina there were more than 350,000 people infected with the corona virus -19, ranked in the top 15 countries with the most cases. The purpose of this paper is to prepare curriculum development in Argentina in the face of the COVID-19 pandemic. The research method used is literature study, collecting information and data through various literatures, books, journals, Argentine government regulations, relevant previous research results. as well as other references. The analysis carried out is the process of preparing the curriculum in Argentina in the face of the covid-19 pandemic with the Saylor curriculum formulation model, which consists of curriculum planning, curriculum implementation, and curriculum evaluation. The Argentine government has issued several regulations and curricula in dealing with the COVID-19 pandemic. CFE Resolution No. 362/2020 decree governing the Distance Education Protocol, with Resolution N° 423/2020 the Ministry of Education of the Nation established the “Advisory Council on Current Return to Classroom Planning”. In the Saylor, Alexander and Lewis model, curriculum changes are implemented in three stages, namely; the curriculum design stage, the curriculum implementation stage, and the curriculum evaluation stage, curriculum changes are made to ensure that citizens continue to receive education.